2021
DOI: 10.5194/bg-2021-39
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sediment and carbon accumulation in a glacial lake in Chukotka (Arctic Siberia) during the late Pleistocene and Holocene: Combining hydroacoustic profiling and down-core analyses

Abstract: Abstract. Lakes act as important sinks for inorganic and organic sediment components. However, investigations of sedimentary carbon budgets within glacial lakes are currently absent from Arctic Siberia. The aim of this paper is to provide the first reconstruction of accumulation rates, sediment and carbon budgets from a lacustrine sediment core from Lake Rauchuagytgyn, Chukotka (Arctic Siberia). We combined multiple sediment-biogeochemical and sedimentological parameters from a radiocarbon-dated 6.5 m sediment… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…It is also possible that longer periods of ice cover compared to Unit 2 and Unit 3 restricted in situ autotrophic production (algae) in the lake. However, these TOC values are high compared to other reported values from Yedoma permafrost (Windirsch et al, 2020;Vyse et al, 2021; Figure 8). Moderately high δ 13 C values, high TIC values, and relatively low TOC (Figure 4) compared to Units 2 and 3 corroborate lower levels of bioproductivity within the lake and indicate input from sources of inorganic carbon during this time (Schirrmeister et al, 2011), as shown in other lake records from Yakutia (Biskaborn et al, 2012).…”
Section: Multiproxy-inferred Paleolimnological Historycontrasting
confidence: 57%
See 4 more Smart Citations
“…It is also possible that longer periods of ice cover compared to Unit 2 and Unit 3 restricted in situ autotrophic production (algae) in the lake. However, these TOC values are high compared to other reported values from Yedoma permafrost (Windirsch et al, 2020;Vyse et al, 2021; Figure 8). Moderately high δ 13 C values, high TIC values, and relatively low TOC (Figure 4) compared to Units 2 and 3 corroborate lower levels of bioproductivity within the lake and indicate input from sources of inorganic carbon during this time (Schirrmeister et al, 2011), as shown in other lake records from Yakutia (Biskaborn et al, 2012).…”
Section: Multiproxy-inferred Paleolimnological Historycontrasting
confidence: 57%
“…Unit 3 is more homogenous than Unit 1 and Unit 2, both in terms of a lack of discernable laminations or other features and homogeneity within the biogeochemical metrics analyzed. Average TOC content is >34 wt% (ranging from 29 to 39 wt%) in this unit, higher than elsewhere along the core and an order of magnitude above most of the reported values for lakes across Yedoma regions (Vyse et al, 2021). Presumably, this period heralded higher levels of bioproductivity and increased nutrient supply to an expanding lake at the study site.…”
Section: Unit 3 (Early Holocene To Present)mentioning
confidence: 53%
See 3 more Smart Citations